2010
DOI: 10.1111/j.1095-8339.2010.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of Centaurea section Acrocentron (Asteraceae) in Iran

Abstract: The taxonomic status of Centaurea section Acrocentron in Iran is briefly reviewed. A critical study of 251 herbarium specimens, and an additional 37 accessions collected specifically for this research, led to the discovery of a new variety, Centaurea irritans var. longispinosa Montazerolghaem, and the revival of another, C. persica var. subinermis, a taxon previously treated as a synonym for about 25 years. A key to all Iranian species of Centaurea section Acrocentron is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Rahiminejad et al [38] found that, among micromorphological characters of Centaurea species, the type and density of epidermal indumentum of leaf and stem were of particular taxonomic value. We recorded two types of non-glandular trichomes on C. sadleriana, including those with thick-walled and thin-walled basal cells, which were more numerous on the abaxial epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Rahiminejad et al [38] found that, among micromorphological characters of Centaurea species, the type and density of epidermal indumentum of leaf and stem were of particular taxonomic value. We recorded two types of non-glandular trichomes on C. sadleriana, including those with thick-walled and thin-walled basal cells, which were more numerous on the abaxial epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be pointed out that characters of the involucre and the involucral bracts are the most important ones in sect. Acrocentron and, in many cases, they are the only useful ones for separating closely related species (Font et al 2002, 2009, Rahiminejad et al 2010, Ferrer-Gallego et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dobrocz.] integra unas 100 especies con distribución principalmente mediterránea, aunque algunas de ellas se extienden por gran parte de la región eurosiberiana (Font et al, 2002(Font et al, , 2009Font, 2007;Rahiminejad et al, 2010), estando asimismo representado por un elevado número de endemismos (Gardou, 1975;Wagenitz, 1975). Esta sección incluye especies perennes, acaules o caulescentes, con tallos no alados, brácteas involucrales medias con apéndice triangular y decurrente, pectinado-fimbriado o más comúnmente pectinado-espinoso.…”
Section: Introductionunclassified